Coordination in dynamic jumping - Wilson, C.; Yeadon, M. R.; King, M. A. (ISBS - Conference Proceedings Archive (Konstanz), 2006)
This study investigated coordination in dynamic jumping using a forward dynamics computer simulation model. A planar eight-segment torque-driven model was used to match the takeoff phase in a recorded running jump for height and recorded jump for distance by varying the torque generator activation timings. Two optimisations were then carried out to maximise height reached and distance travelled for each set of initial conditions used in the matching simulations. Although for each set of initial conditions, the order of activation onset timing was different for the two optimisations, the timing of activation onset in the optimisations for height and distance using the same initial conditions was very similar. This study has shown that the optimal activations are more a function of the initial conditions than the selection of maximal height or maximal distance.